Heat-tolerant algal symbionts may prevent extirpation of the threatened elkhorn coral, Acropora palmata, in Florida during intensifying marine heatwaves - Richard F. Karp; Fabrizio Lepiz-Conejo; Shayle B. Matsuda; Bryce Corbett; Alexandra D. Wen; Joseph D. Unsworth; Martine D’Alessandro; Ken Nedimyer; Amelia Moura; Erinn M. Muller; Zachary Craig; Diego Lirman; et al. (Coral Reefs, 2025)
The elkhorn coral, Acropora palmata , was historically a major reef-building species in the Caribbean, but has suffered devastating declines in recent decades. Despite significant restoration efforts in Florida, the marine heatwave of 2023 caused severe bleaching and mortality to both wild and restored colonies. To understand the disastrous impacts, we evaluated the variation in heat tolerance among Florida’s A. palmata population prior to the event. In 2022, we used rapid acute heat stress assays to assess the thermal tolerance of 172 adult colonies (125 unique genets) from four nurseries. We found variation in thermal tolerance (4.17°C range in ED50) that was attributed to nursery location (17.2% of variation), genet (25.9%), and symbiont abundance (15.6%). Algal symbiont type, however, was the strongest predictor of thermal performance, with the few (n = 10) colonies hosting Durusdinium being, on average, 1.9°C more thermally tolerant than corals hosting Symbiodinium . This difference would have decreased the effective heat stress accumulation during the 2023 event by ~92%. Therefore, despite considerable variation in thermal tolerance among Florida’s elkhorn corals, hosting Durusdinium appears to be the most effective mechanism for surviving such extreme heat stress. These findings suggest that restoration strategies that focus on rearing sexually derived A. palmata recruits with Durusdinium , followed by outplanting to suitable environments, may improve survival during future heatwaves. Combined with efforts to introduce additional elkhorn diversity from populations outside Florida, these approaches may be the most effective interventions to promote the continued survival of Florida’s elkhorn corals in the face of rapid climate change.